Rare germline ATM variants of uncertain significance in chronic lymphocytic leukaemia and other cancers - Petrackova, Anna; Savara, Jakub; Turcsanyi, Peter; Gajdos, Petr; Papajik, Tomas; Kriegova, Eva (British journal of haematology, 2022)
Germline pathogenic ATM (ataxia-telangiectasia mutated) variants are associated with the risk of multiple cancers; however, genetic testing reveals a large number of ATM variants of uncertain significance (VUS). Here, we studied germline ATM variants occurring in a real-world cohort of 336 patients with chronic lymphocytic leukaemia (CLL) and public cancer whole-exome/genome-sequencing datasets (445 CLL, 75 mantle cell lymphoma, 216 metastatic breast cancer, 140 lung cancer patients). We found that two-thirds of rare germline ATM variants are pathogenic (18%-50%) or VUS-predicted pathogenic (50%-82%), depending on cancer type and reaching a prevalence of up to 8%, and one-third are VUS-predicted benign. Patients with both pathogenic and VUS-predicted pathogenic variants, all heterozygous, mostly missense, are more predisposed to biallelic ATM inactivation by acquiring deletion (del)11q than patients without these variants, similar to patients with somatic ATM variants. A functional assay of ATM activity in primary CLL cells proved that VUS-predicted pathogenic ATM variants partially reduce ATM activity and concurrent del(11q) leads to complete loss of ATM activity. The rare germline variants were associated with reduced progression-free survival in CLL on novel agents, comparable to somatic ATM or TP53 disruptions. Our results highlight the need to determine the pathogenicity of VUS in clinically relevant genes such as ATM.
Keywords: ženské pohlaví; zárodečné mutace; kohortové studie; Ataxia Telangiectasia Mutated Proteins; nádory prsu; Germ-Line Mutation; Cohort Studies; lidé; Female; Leukemia, Lymphocytic, Chronic, B-Cell; Lymphoma, Mantle-Cell; Breast Neoplasms; lymfom z plášťových buněk; chronická lymfatická leukemie; ATM protein; Humans